2020
DOI: 10.1111/irv.12691
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on clinical characteristics, hospitalization and mortality of patients with influenza‐related illness at a tertiary care centre in Malaysia

Abstract: Background:Age is an established risk factor for poor outcomes in individuals with influenza-related illness, and data on its influence on clinical presentations and outcomes in the South-East Asian settings are scarce. The aim of this study was to determine the above among adults with influenza-related upper respiratory tract infection at a teaching hospital in Malaysia. Methods:A retrospective case-note analysis was conducted on a cohort of 3935 patients attending primary care at with URTI symptoms. Demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
1
15
0
2
Order By: Relevance
“…On the other hand, sore throat, conjunctival hyperemia, tearing, sneezing, sputum production, dyspnea, vomiting and rhonchi at pulmonary auscultation were more frequently described in influenza group than COVID-19 group with statistically significant differences. Sore throat was a well-known symptom in influenza, found in about 30e40% of the patients in the literature as in our study [25,27,28]. Conjunctival hyperemia seems to be rare with COVID-19, less than 5% of cases in our study vs 30% of cases in influenza group (p < 0.001).…”
Section: Comparison Of Patients With Covid-19 and Patients With Influsupporting
confidence: 50%
See 1 more Smart Citation
“…On the other hand, sore throat, conjunctival hyperemia, tearing, sneezing, sputum production, dyspnea, vomiting and rhonchi at pulmonary auscultation were more frequently described in influenza group than COVID-19 group with statistically significant differences. Sore throat was a well-known symptom in influenza, found in about 30e40% of the patients in the literature as in our study [25,27,28]. Conjunctival hyperemia seems to be rare with COVID-19, less than 5% of cases in our study vs 30% of cases in influenza group (p < 0.001).…”
Section: Comparison Of Patients With Covid-19 and Patients With Influsupporting
confidence: 50%
“…About respiratory symptoms, sputum production and dyspnea were statistically more frequents in influenza group than in COVID-19 group (respectively 52% vs 29%, p ¼ 0.010 and 59% vs 34%, p ¼ 0.007). In a study with 470 patients with confirmed influenza, 286 (64%) had a productive cough [27]. Dyspnea was also described in more than half of patients with influenza A [28,30].…”
Section: Comparison Of Patients With Covid-19 and Patients With Influmentioning
confidence: 99%
“…Age and pre-existing CVD have been associated with higher mortality in critically ill patients with viral infection. 23 , 24 , 25 Older patients may have more comorbidities (i.e., CAD, hypertension, chronic kidney disease and diabetes) and a higher rate of CV complications. In fact, no patients over 80 years had survived at the end of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association of sociodemographic factors (age, male sex, and smoking) with severe COVID-19 is consistent with reports of other infectious diseases (e.g., influenza virus and SARS in 2003). [27][28][29] There are several plausible mechanisms. Older age is linked to reduced immune reaction, more comorbidities, and limited organ reserve.…”
Section: Discussionmentioning
confidence: 99%